Comparative Analysis of Public Perceptions of Tax Justice and Public Responses to Changes in the Tax System - Saputra, Tri Eka; Prabowo, Rahmat Eko (Advances in Taxation Research, 2025)
Purpose: This study examines public perceptions of tax justice and responses to systemic tax reforms, particularly in the context of digitalization and reform-driven economies like Indonesia. It investigates how distributive and procedural fairness, financial literacy, and socio-economic dynamics shape trust, compliance, and acceptance of tax policies. Research Design and Methodology: The study employs a qualitative approach, using a Systematic Literature Review (SLR) to synthesize insights from recent theoretical and empirical studies. Integrating key findings from interdisciplinary research explores the relationship between tax justice perceptions, digitalization, financial literacy, and public trust in tax reforms. Findings and Discussion: The study reveals that perceptions of tax fairness significantly influence public trust and compliance. Distributive justice ensures equitable tax burdens aligned with economic capacity, while procedural justice emphasizes transparency and inclusive in policy implementation. Financial literacy moderates the relationship between perceived fairness and voluntary compliance, enhancing public understanding of taxation benefits. Digitalization offers efficiency but presents challenges of inclusivity, particularly for marginalized groups. The findings highlight the importance of tailoring reforms to socio-economic and cultural contexts to foster trust and acceptance. Implications: The study underscores the need for transparent, equitable, and inclusive tax policies. Policymakers should prioritize public education on financial literacy, ensure equitable digital tax systems, and promote participatory governance in tax reform processes. These measures will enhance compliance, strengthen public trust, and promote sustainable economic development. Future research should empirically validate these relationships and explore cross-country comparisons to deepen understanding of taxation dynamics.